Konsentrasi PEG 6000 dan Senyawa Aditif Buffer Fosfat yang Diperlukan dalam Pemurnian Soybean Mosaic Virus - Y. B. Sumardiyono; Susamto Somowiyarjo; Wuye Ria Andayani (Jurnal Perlindungan Tanaman Indonesia, 1995)
The objective of study was to determine the concentration of PEG 6000 for precipitation of virus particles, and additive substance added to the resuspension buffer, during the purification of Soybean Mosaic Virus isolated from Yogyakarta. The result showed that precipitation with PEG 6000 of 6 per cent at final concentration, followed by either two or three cycles differential centrifugation and the virus obatained from each centrifugation resuspended in Phosphate buffer 0.05 M contained NaCl 0.1 M added with 0,005 M Na-EDTA, and then subjected to 10-50 per cent sucrose density gradient centrifugation. The purified virus obtained was infective, with the ultraviolet absorption maximum at 260 nm and minimum at 247 nm, ratio A280/A260 was 0.7343. based on extinction coefficient at 260 nm = 2.4, the yield was 0.306 mg/100 g infected leaves. SDS-PAGE indicating that coat protein molecule weight was 29.71 kD.